Synthesis of some new ,3-oxazepine derivativesand evaluation of antibacterial activitv - H.A. Al-Somaidaie, Gazwan; Y. Majeed, Ismeel; K. Jassim, Ibtisam (Tikrit Journal of Pharmaceutical Sciences, 2023)
This paper contained the synthesis of some new derivatives of 1,2,4-ttazole ring from the reactions of 3-amino 1,2,4-triazole derivatives (I) with different substituted benzaldehyde (in absolute .ethanol with present glacial acetic acid as catalyst) to prepare Schiff bases (IIa-c). The prepared new Schiff bases (IIa-c) reacted with maleic anhydride or 2-nitro phthalic anhydride in dry benzene to give oxazepines compounds (IIIa-e) (7-membered ring). The synthesized compounds were elucidated by some spectroscopy methods (IR ,UV and Elemental analysis (C.H.N)) besides the TLC was used to check the products. Tire biological activities of some prepared compounds (IIa, IIIa-e) were also studied asainst four different kinds of bacteria.